2018
DOI: 10.1107/s2059798318000050
|View full text |Cite
|
Sign up to set email alerts
|

A DNA structural alphabet provides new insight into DNA flexibility

Abstract: DNA is a structurally plastic molecule, and its biological function is enabled by adaptation to its binding partners. To identify the DNA structural polymorphisms that are possible in such adaptations, the dinucleotide structures of 60 000 DNA steps from sequentially nonredundant crystal structures were classified and an automated protocol assigning 44 distinct structural (conformational) classes called NtC (for Nucleotide Conformers) was developed. To further facilitate understanding of the DNA structure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…At the intercalation cavity there is evidenceo fb ackbone disorder,a nd the phosphate group of residue G10 was modelleda samixture of B I and B II conformations. [34] As we have previously seen with the unsubstituted dppz and this sequence, [25] there is ar eversal in the conformation of the terminal guanine base G10, so that it stacksi nasyn conformationw ith the negative, and normally major groove face of the guanine stacked over the pyrazine ring, and aligning the 2-NH 2 vector direction of the guanine with one of the ligand CN groups. Furtherd etails of map quality and water structure are shown in FiguresS9a nd S10.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…At the intercalation cavity there is evidenceo fb ackbone disorder,a nd the phosphate group of residue G10 was modelleda samixture of B I and B II conformations. [34] As we have previously seen with the unsubstituted dppz and this sequence, [25] there is ar eversal in the conformation of the terminal guanine base G10, so that it stacksi nasyn conformationw ith the negative, and normally major groove face of the guanine stacked over the pyrazine ring, and aligning the 2-NH 2 vector direction of the guanine with one of the ligand CN groups. Furtherd etails of map quality and water structure are shown in FiguresS9a nd S10.…”
Section: Resultsmentioning
confidence: 64%
“…Analysis of DNA dihedral angles was performed using DNATCO. [34] Structural diagrams were created using PyMol (Schrçdinger).…”
Section: Macromolecular Crystallographymentioning
confidence: 99%
“…A smaller fraction of approximately 20% of the steps have B-A conformations, while 15% are in BII or mixed BI/BII configurations. The smallest fraction, 10%, of the dinucleotide steps adopt A and A-to-B forms [ 68 ]. Analogous to the broadly accepted structural heterogeneity of proteins, especially intrinsically disordered peptides, we observe that the DNA dodecamer accesses a larger number of classes, ranging from the A to the B form, which we characterized by a classification using the structural alphabet of DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The structural datasets demonstrate the structural variability of DNA and proteins, knowledge which has been necessary for understanding how DNA and proteins adopt their structures upon binding to ligands or other biomolecules in signaling processes. For example, it has been shown that DNA can adopt a large variety of structural conformers in addition to the canonical ’B’ form found by Watson and Crick [ 65 ], as defined in the structural alphabet of DNA [ 65 , 66 , 67 , 68 ]. The variety of possible structures ranges from double to triple and quadruple helices [ 69 , 70 ], DNA junctions, as well as parallel helices and hairpins [ 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assignment of DNA conformations was introduced as a web server that is currently available at https://dnatco.datmos.org/ v2 (Č erný et al, 2016). The evolved description of DNA conformations was based on a nine-dimensional space of parameters containing seven backbone torsions and two torsion angles around glycosidic bonds within a DNA dinucleotide step (Schneider et al, 2018). This approach has also successfully been applied to the identification of the key structural differences between a DNA interacting with regulatory proteins and in the nucleosome core particle, explaining the structural details of different mechanisms of DNA bending (Schneider et al, 2017).…”
Section: Introductionmentioning
confidence: 99%